Umbilical artery doppler and biophysical profile score: a study of their efficacy in pregnancy induced hypertension and intrauterine growth retardation - Meherishi, Shuchita Sharma; Mangal, Suchika (International Journal of Research in Medical Sciences, 2017)
Background: Accurate diagnostic tests to identify fetuses at risk for in-utero death or injury have long been an important goal for obstetricians and perinatologists. Umbilical Artery Doppler and biophysical profile score are two tests available for antepartum fetal surveillance. Methods: The study consisted of 100 patients with either presence of PIH (30) or IUGR (28) or both (42). Testing was begun was at 33 weeks. UAD was performed; S/D, RI and PI indices were calculated. Fetal BPS was determined. Results: Fetal weight was estimated to be less than 2kg in last scan was 23.52% cases in pih/ iugr group versus 6.4% in controls whereas incidence of oligohydramnios was 29.5% versus 91.17% respectively, and number of babies admitted to NICU was 11.47% versus 70.58% respectively Conclusions: Doppler and biophysical studies can greatly help in arriving at an appropriate strategy for management.